Targeted microbiome metabolomics reveals flaxseed oil supplementation regulated the gut microbiota and farnesoid X receptor pathway in high-fat diet mice - Chen Yang; Zhenxia Xu; Qingde Huang; Xu Wang; Fenghong Huang; Qianchun Deng (Food Science and Human Wellness)
Flaxseed oil (FSO) rich in n-3 polyunsaturated fatty acids (PUFAs) can protect against obesity and insulin resistance, but the underlying mechanism is unknown. An integrative multiomics of the microbiome and targeted metabolomics approach was performed to investigate the possible pathway for flaxseed oil supplementation on reducing serum total cholesterol, triglyceride and epididymal adipose in high-fat diet mice. FSO ameliorated the gut microbial dysbiosis by increasing the community diversity and the abundance of Clostridiales and Ruminococcaceae. These effects were associated with the regulation of bile acid (BAs) in the feces. FSO reduced the concentrations of conjugated BAs, such as cholic acid, tauro-α-murocholic acid, and tauro-ursodesoxycholic acid in feces, which in turn inhibit the intestinal farnesoid X receptor (FXR)-fibroblast growth factor (FGF) 15 signaling pathway. Further analysis revealed that FSO activated FXR in the liver and regulated downstream gene expression (SHP, SREBP-1c, and CPT-1a), which promoted lipolysis and inhibited lipogenesis. The results of this study suggest that FSO modulates serum lipid concentrations by regulating the gut microbiota, FXR-FGF15 signaling and BA metabolism.